Pengaruh Pola Asuh Otoriter terhadap Psychological Well Being pada Usia Remaja Awal di MTs NU Trate Gresik - Ananda Fitri; Nadhirotul Laily; Awang Setiawan Wicaksono (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research was conducted to test whether there is an influence between authoritarian parenting on psychological well-being in early adolescents. The number of samples in this study was 198 students with an age range of 12 to 15 years. This research uses a quantitative approach with a correlational type of research. Based on the analysis results obtained from the simple linear regression test, a significance value of 0.002 was obtained. This means that the significance value is smaller than 0.05. So it can be concluded that authoritarian parenting has an influence on psychological well-being in early adolescence. From the results of the regression coefficient value of minus, namely -0.019, it can be said that authoritarian parenting has a negative effect on psychological well-being in early adolescence. This means that the higher the authoritarian parenting style, the lower the level of psychological well-being in early adolescence. For future researchers, it is recommended to use other theories that have not been used in this research, for example Riberio's theory. Apart from that, to develop further research, we can also use internal factors that can influence psychological well-being, for example gender factors, evaluation of life experiences and locus of control.